KANDUNGAN SAKARIN DALAM MINUMAN ES SIRUP DI SD KECAMATAN KOTA BARU JAMBI - Rina Fauziah; Zunindra Zunindra; Supriadi Supriadi (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Snack food security need to considered because it plays an important role in the growth and development of children of school. The food often becomes the source of poisoning was snacks and desserts. The goal to analyze levels of artificial sweeteners saccharin as food additive in ice syrup.Type of research using survey method. Population is ice syrup sold in the canteen elementary school. Sample is 44 kind of ice syrup sold in canteen elementary school. Primary data was obtained through interviews with the seller of ice syrup and examination the Laboratory Academy health Analysis Jambi. Secondary data obtained from Department of Education and Culture of Jambi city related to number of elementary schools in district Kota Baru. The result show that out of 44 samples checked all contain saccharin and 13 samples exceeds standards. Number of traders selling drinks containing saccharinbecause the low level education, lack of information relating to food additives and the absence security of the health service or BPOM Jambi.Keywords : saccharin, ice syrup